Pediatric neuro-oncology: Highlights of the last quarter-century - Phoebe Power; Joelle P Straehla; Jason Fangusaro; Pratiti Bandopadhayay; Neevika Manoharan (Neoplasia: An International Journal for Oncology Research)
The last quarter century has heralded dramatic changes in the field of pediatric neuro-oncology, with the era defined by profound developments in the understanding of the biological underpinnings of childhood central nervous system (CNS) tumors and translational therapeutics. Although there have been momentous strides forward in biologic, diagnostic, therapeutic, and experimental domains, considerable challenges remain and CNS tumors remain the leading cause of pediatric cancer-related mortality. Here, we review the significant advances in the field of pediatric neuro-oncology over the last 25 years and highlight ongoing hurdles facing future progress.